"There is no alternative.": Treatment decision-making in lung cancer patients with limited prognosis : results of a qualitative interview study - Unsöld, Laura; Deis, Nicole; Siegle, Anja; Thomas, Michael; Villalobos Bollen, Matthias Americo (European journal of cancer care, 2024)
Objective. Decision-making in advanced cancer with a limited prognosis is particularly challenging: constantly evolving therapeutic algorithms with new treatment options that show marginal benefits have to be balanced with end-of-life decision-making. But existing decision support tools for advanced cancer patients are rare, not routinely used in clinical practice and do not sufficiently meet patients’ needs. Therefore, our project explores the experienced decision-making process in advanced lung cancer to derive recommendations for the use of shared decision-making in this context. Methods. 20 semistructured interviews with lung cancer patients, their relatives, and healthcare professionals were conducted. All data were transcribed verbatim and analyzed with a thematic content analysis. Results. The decision-making process of advanced cancer patients is mainly characterized by a lack of perceived options. Physicians do not adequately present palliative care as an alternative or additional support for these patients. Being confronted with limited options that only include active cancer treatment patients tend to choose a more paternalistic decision model leaving the treatment decision to their physicians and accepting aggressive treatments uncritically. Conclusion. A paternalistic decision-making model in advanced cancer may neglect individual wishes, values, and preferences of patients and promote a feeling of powerlessness. Empowerment of these patients is needed with context-specific SDM tools and trainings of professionals to avoid overtreatment and facilitate the timely integration of palliative care. This trial is registered in DRKS00023674.
Gesehen am 19.02.2025